Bioavailability of Zn as affected by root-induced changes of pakchoi cultivars with different Zn efficiencies - Hu, Xue-Yu; Li, Xue-Yuan (Journal of soils and sediments, 2009)
Background, aim, and scope The Zn content in the human body is tremendously higher than that in the plant. It is vulnerable to Zn nutrition deficiency in the human body. Those who consume less animal products are subject to Zn deficiency and mainly live in the developing regions. The preventive measures against Zn deficiency in the human body, for example, Zn supplements from chemicals and Zn-fortified food, are expensive and often unattainable. We have been working on finding solutions to Zn malnutrition by screening Zn-efficient varieties of crops which can absorb more Zn from Zn-deficient soils and transfer more Zn to the edible part of crops. Pakchoi is a popular vegetable in many parts of the world. The Zn deficiency in the human body could be rectified by consuming Zn-efficient pakchoi cultivars. Rhizosphere is the 'hotspot' for plant-soil-microbe interactions, and the rhizospheric interactions play a key role in the micronutrient acquisition. However, little attention has been paid to the rhizosphere effects of different plant genotypes on the expression of nutrient efficiency. The aim of this study was to examine the difference of rhizosphere effect between two pakchoi cultivars with different Zn efficiencies. Materials and methods A Zn-deficient calcareous purple soil was collected from central China. There were two Zn treatments, one with Zn addition (5 mg kg⁻¹ soil) and the other, which acts as a control, with no Zn addition. Two pakchoi cultivars were Wuyueman of Zn-efficient and Heiyoubaicai of Zn-inefficient plants. Ten seeds of each pakchoi cultivar were sown in the rhizobag. The plastic pot was filled with 0.8 kg soil with 37% of the soil in the rhizobag. The seedlings were harvested on day 45 after planting. The rhizosphere and bulk soil samples were analyzed for their physical and chemical properties, microbial biomass, and Zn concentrations. Zn in the plants was also determined. Results The cultivar Wuyueman demonstrated a much higher depletion rate of available Zn in the rhizosphere than did the cultivar Heiyoubaicai. The available Zn in the rhizosphere of Wuyueman was lower in the rhizosphere soil (0.47 mg kg⁻¹) compared with that in the bulk soil (1.08 mg·kg⁻¹), and the depletion rate of available Zn was 56.5% under Zn deficiency. This was closely associated with the capacity of cultivar Wuyueman to take up more Zn from the soil, especially under Zn-limiting conditions. The rhizosphere pH of pakchoi cultivars was lower than that in the bulk soil, while the microbial biomass carbon in the rhizosphere was significantly higher than that in the bulk soil. Under Zn-deficient conditions, the rhizosphere pH of the cultivar Wuyueman was lower but the microbial biomass carbon was higher than those of the cultivar Heiyoubaicai. Discussion Soil-available Zn was substantially depleted in the rhizosphere of two pakchoi cultivars, with the greater depletion rate being found in the cultivar Wuyueman rather than in the cultivar Heiyoubaicai, especially under Zn-deficient conditions. This was related to the mobilization of Zn induced by the plants with different Zn efficiencies and, thus, Zn bioavailability in the rhizosphere. The pH decrease and the increase of microbial biomass carbon in the rhizosphere of the cultivar Wuyueman might have contributed to the translocation of Zn in its rhizosphere, which allows Zn to be absorbed more easily by Wuyueman than by Heiyoubaicai. This suggests that root-induced changes in the rhizosphere of pakchoi have a certain effect on the expression of zinc efficiency. Conclusions Root-induced changes mobilized Zn in the rhizosphere of two pakchoi cultivars and increased its bioavailability. The rate of Zn mobilization was higher in the rhizosphere of the Zn-efficient cultivar than that of the Zn-inefficient cultivar at low Zn levels. Recommendations and perspectives Root-induced changes in the rhizosphere are important factors for the nutrient dynamics and, thus, also for the mineral nutrition of plants. Soil conditions near the roots are different from those in the bulk soil. Many results have shown that these differences depend on soil properties, fertilizer application, plant species, and other factors. Further research should focus on the environmental effects of the rhizosphere on nutrient availability.